Te conheço de outros carnavais : a linguagem das escolas de samba nos circuitos da comunicação entre Brasil e Portugal - Silva, José Maurício Conrado Moreira da (2011)
This investigation has as study object the language of the parades of school of samba in the communicative flows between Brazil and Portugal. In century XVI, an old Portuguese and colonial carnival arrived at Brazil colony brought by formers. From years 1970 of century XX, it occurred an inversion on those flows when Brazil started to export new languages, as of the school of samba (derived from the colonial Carnival) and soap operas. This process was after intensified the after the Revolution dos Cravos, a fact that was responsible for reopening the cultural and political boundaries of Portugal. This thesis analyzes this communicative circuit between Brazil and Portugal that start to characterize a species of context post-colonial of the lusophonie, understood in this research as being a media environment for the countries that use the Portuguese language. To compose the theoretical grating this work uses concepts from authors who argue about lusophonie (Cunha, 2005), the carnival (Bahkthin, 1998; Damatta, 1997), evolutive theories of culture (Katz & Greiner, 2004, 2005, 2009), processes of cultural hybridization (Canclini, 2001), post-colonials theories (Bhabha, 2003, Hall, 2003), semiotics (Santaella & Noth, the 2004) and communication (Mcluhan, 1997). The methodology understands bibliographical, internet, video and musical data the inquiry and its correlation with the other sources of information, proceeding from the contact with the schools of samba in Portugal, made possible for the research of field that was carried through with the support of the University of the Minho, in cities and Portuguese villages that practice the carnival ritual. The main results is about the conclusion that the imitation of the Brazilian parades in the foreign environment of Portugal is a complex process and sets in motion what this if calling "market of languages . This market of languages represents an inversion of sensible in the habitual circuits, therefore Brazil, the former-colony, now is exporting languages to the former-metropolis: schools of samba, soap opera, etc. The unfolding of this quarrel can be identified in debates of authors as Boaventura de Souza Santos whose project of research ALICE (2011) argues that Europe needs to recognize itself in the mirrors of the worlds that helped to create. In this inquiry, it is considered, therefore, that in market of languages between Brazil and Portugal, the samba schools, as process derived from the colonial Carnival, is a possible metaphor of these mirrors